Spontaneous spinal cerebrospinal fluid venous-fistula treated with transvenous embolization: A case report - Aljuboori, Zaid; McGrath, Margaret; Essibayi, Muhammed Amir; Zaidi, Saif; Hallam, Danial; Ghodke, Basavaraj (Scientific Scholar, 2021)
Background: Spinal cerebrospinal fluid venous fistula (CVF) is a recognized cause of chronic positional headache and spontaneous intracranial hypotension (SIH). It occurs due to an aberrant connection formed between the spinal subarachnoid space and an adjacent spinal epidural vein. The diagnosis of CVF can be difficult to establish but can be documented utilizing advanced imaging techniques (e.g., enhanced MR myelography/digital subtraction myelography). Their treatment involves surgical ligation of the involved nerve root, imaging-guided epidural blood patching, and/or endovascular embolization. Here, we report a 40-year-old male who presented with a symptomatic lumbar CVF successfully treated with transvenous embolization. Case Description: A 40-year-old male presented with several months of positional headaches. The MRI of the brain showed diffuse pachymeningeal enhancement consistent with the diagnosis of SIH. Although the MR of the lumbar spine was unremarkable, the MR myelogram with digital subtraction imaging showed a CVF at the L2 level. Following transvenous embolization (i.e., through the Azygous vein), the patient’s symptoms fully resolved. Conclusion: Spinal CVF are rare and may cause chronic headaches and symptoms/signs of SIH. In this case, an MR myelogram with digital subtraction images demonstrated the anomalous connection between the spinal subarachnoid space and an adjacent spinal epidural vein at the L2 level. Although open surgical ablation of this connection may be feasible, less invasive techniques such as endovascular embolization should become the treatment of choice for the future management of CVF. ©2021 Published by Scientific Scholar on behalf of Surgical Neurology International
Keywords: Cerebrospinal fluid; Embolization; Fistula; Venous